A chiral molecular cage comprising diethynylallenes and N-heterotriangulenes for enantioselective recognition - Miguez‐Lago, Sandra; Gliemann, Bettina D.; Kivala, Milan; Cid, María Magdalena (Chemistry - a European journal, 2021)
Chirality, a characteristic tool of molecular recognition in nature, is often a complement of redox active systems. Scientists, in their eagerness to mimic such sophistication, have designed numerous chiral systems based on molecular entities with cavities, such as macrocycles and cages. In an attempt to combine chirality and redox-active species, in this contribution we report the synthesis and detailed characterization of a chiral shape-persistent molecular cage based on the combination of enantiopure diethynylallenes and electron-rich bridged triarylamines, also known as N-heterotriangulenes. Its ability for chiral recognition in solution was revealed through UV/vis titrations with enantiopure helicenes.
First published: 09 August 2021
In memory of Professor François Diederich
Gesehen am 23.09.2022